2022
DOI: 10.24914/jeb.v25i1.3598
|View full text |Cite
|
Sign up to set email alerts
|

Top management gender and earnings management

Abstract: Top management (including CEOs and CFOs) are firms’ crucial resources, especially in preparing financial statements that are used by external parties in making decisions. Besides, prior literature also demonstrates that top managers’ gender affects their decisions. Accordingly, this study seeks to analyze the effect of CEO and CFO gender on earnings management in manufacture company. We use the modified Dechow-Dichev Model by Mcnichols (2002) to identify earnings management. The results show that female CEOs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The results of this test are contrary to Setyaningrum et al (2019) who found that female CEOs have a negative and significant effect on fraud in the form of earnings management. However, the results of testing the first hypothesis are in line with Deruvensi & Kristianti (2022) who proved that female CEOs do not affect accounting fraud. Harris et al (2019) assert that female CEOs do not necessarily reduce fraud, because female and male CEOs show very similar cheating behavior.…”
Section: Female Chief Executive Officer and Financial Reporting Fraudsupporting
confidence: 75%
See 2 more Smart Citations
“…The results of this test are contrary to Setyaningrum et al (2019) who found that female CEOs have a negative and significant effect on fraud in the form of earnings management. However, the results of testing the first hypothesis are in line with Deruvensi & Kristianti (2022) who proved that female CEOs do not affect accounting fraud. Harris et al (2019) assert that female CEOs do not necessarily reduce fraud, because female and male CEOs show very similar cheating behavior.…”
Section: Female Chief Executive Officer and Financial Reporting Fraudsupporting
confidence: 75%
“…Luo et al (2020); Maulidi et al (2022); found that women are more risk-averse and committed to ethical practices than men in leadership positions in companies and female CFOs tend not to engage in risky and unethical financial reporting fraud compared to male CFOs. Conversely, Deruvensi & Kristianti (2022) prove that female CFOs do not affect reducing accounting fraud. Ahmadi et al (2018);and Brahma et al (2021) state that the role of women as commissioners on boards of companies is very important.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…07, No. 02, December 2022p-ISSN: 2527-4309, e-ISSN: 2580-14815 th Accreditation Rating: January 14, 2019 A review of the theory used in Earnings Management research shows that several theories can be used as alternatives in explaining Earnings Management, such as avoidance theory (Nadhifah & Arif, 2020), fraud triangle theory (Sesaria & Manda, 2021), family ownership theory (Dwiyanti, 2017), role alignment theory (Karina, 2021), resource dependency theory (Deruvensi & Kristianti, 2022), legitimacy theory (Akbar & Purnomo, 2021), stakeholder theory (Senjaya et al, 2021), political theory (Karina, 2021), SEW theory (Senjaya et al, 2021), stakeholder theory (Nadhifah & Arif, 2020), capital structure theory (Kamil & Ariyani, 2017).…”
Section: Figure 4 Theoriesmentioning
confidence: 99%
“…The scope of research is also a concern in this research to find out what was the concern of previous researchers. A total of seven studies discuss Earnings Management in manufacturing companies (Deruvensi & Kristianti, 2022;Hidayat et…”
Section: Scope Of Studymentioning
confidence: 99%